65 Changes in anticoagulant use in England over two decades: 1998-2018. (17th July 2020) - Sotto, Imelda; Arefin, Rashad; Mouyis, Kyriacos; Toma, Tania; Lee, Lok Yee; Harding, Daniel; Perez, Carlos; Mohammad, Hira; Ng, Sher May; Patel, Hitesh; Hayward, Carl
Abstract : Introduction: The European Society of Cardiology guidelines on the management of Atrial Fibrillation (AF) advocate the use of direct oral anticoagulants (DOACs) over warfarin. Their use is also licenced for the treatment of pulmonary embolism and deep vein thrombosis. DOACs have superior efficacy in stroke reduction, reduced rates of intracranial haemorrhage and improved overall mortality. DOACs are safer, easier to use and don't require monitoring. Aims: We sought to describe changes in prescriptions for anticoagulants over the 20 years from 1998-2018 and to describe the financial implications of the shift away from warfarin. Methods: We conducted a comprehensive nationwide retrospective study. Data were obtained from the Prescription Cost Analysis system, which holds information on every prescription dispensed in the community in England, covering a population of more than 50 million people. We obtained data for warfarin, dabigatran, rivaroxaban, apixaban and edoxaban from 1998 to 2018. Results: There was a linear increase in warfarin prescriptions from 1998 to 2014 but this plateaued in 2015. Thereafter there has been a linear decrease in prescriptions for warfarin. Conversely, total prescriptions for all DOACs combined has increased exponentially in the same time frame and for the first time, there were more prescriptions for DOACs than warfarin in 2018 (9.3 million prescriptions for DOACs vs. 8.2 million prescriptions for warfarin). Rivaroxaban and Apixaban are the most commonly prescribed DOACs by a significant margin. In 2018 the cost of prescriptions for all DOACs combined was £458.6 million compared to £8.9 million for warfarin prescriptions. Conclusion: In 2016 prescriptions for warfarin fell for the first time in 18 years. Within 2 years, DOAC prescriptions have surpassed warfarin prescriptions and warfarin use has continued to decline. This trend has a financial cost in terms of prescriptions with spending on DOACs being 50-fold more than those of warfarin in 2018. The additional cost of warfarin, however, includes anticoagulation clinics and there is no data available to suggest that there has been a reduction in the number of anticoagulation clinics in line with the reduction in warfarin use. Despite this increased cost, the overall safety benefits, ease of use and lack of monitoring supports the continued use of DOACs and there seems no reason to think these trends are likely to change in the near future. Conflict of Interest: nil